Original technique for preoperative preparation of patients and intraoperative localization of parathyroid adenomas - PASTA, V. (G Chir, 2015)
Surgical approach of single parathyroid adenoma treatment is turning to a less invasive surgery, allowing us to obtain better aesthetic results, reduction of duration of surgical operation, reduction of post-operative morbidity and hospital stay. Tc99(m)-sestaMIBI scintigraphy is mainly performed for preoperative localization of parathyroid adenomas. Our technique is instead based on the possibility to inhibit the interference of Tc99(m)-sestaMIBI uptake of the thyroid gland by means of the administration of Lugol’s solution. Indeed, to confirm the identification and removal of the hyperfunctional parathyroid, it is accepted as adequate an ex vivo radioactivity count of the adenoma 20% or 40% greater than the value of the post-excisional background radioactivity, in association or not with intraoperative measurement of PTH. This method allows us to perform surgery with no timetable restriction, and to clearly distinguish the radioactivity of parathyroid adenoma from that of the surrounding tissues and thyroid gland.